Evaluation of Leakage Currents of Semiconductor Packages Due to High-Voltage Stress Under an Immersion Cooling Environment - Kyuhae Min; Taejun Kang; Tae Yeob Kang; Jae-Bum Pyo (Applied Sciences)
As data centers expand, immersion cooling systems are gaining attention for thermal management of memory devices. To enable widespread adoption, it is essential to evaluate the impact of coolants on the reliability of memory packages. In this study, high-voltage direct current (DC) stress tests were conducted on commercial dynamic random access memory (DRAM) packages in both single-phase coolant and air environments to analyze heat generation and electrical characteristics. A DC voltage ranging from 2.5 to 3.1 V, which is higher than the regular operating voltage of 1.2 V, was applied. Temperature changes were measured using an infrared camera in the air, and a contact-based thermometer in the coolant. The leakage current was also evaluated through I-V curve analysis. Heat generation and changes in leakage currents were not significant in either environment until the applied voltage stress exceeded approximately twice the standard voltage (2.5–2.8 V). However, the package’s degradation accelerated when the applied voltages exceeded 3.0 V, demonstrating a nonlinear increase in temperature and leakage current.